The Anthropocene Age Reveals the Insanity at the Heart of Western Christian Religious Experience - LaMothe, Ryan (Pastoral psychology, 2024)
This article claims that the Anthropocene Age reveals the tragic insanity that lies at the core of religious experiences informed by Hebrew and Christian scriptures. In brief, I claim that Western Christianity and its apparatuses produce beliefs, which are an integral part of persons’ religious experiences, that give rise to an ontological rift between human beings and other species. This rift and its attendant beliefs are evident in how religious individuals and communities have (1) overlooked or disavowed the singularities and sufferings of other species, (2) used attendant instrumental epistemologies to justify the exploitation of Othered species (and Othered human beings) and the Earth, and (3) sought to force nature to adapt to human needs and desires. The article addresses the psychological dynamics and consequences of the ontological rift, which further exposes the madness that attends religious experiences that rely on apparatuses of the ontological rift. The article ends with a brief discussion of an antidote, namely, inoperativity.